2-6/13÷9/26-2/3=?
5个回答
=2-6/13×26/9-2/3
=2-4/3-2/3
=2-(4/3+2/3)
=2-2
=0
望采纳
相关问题
2-6/13÷9/26-2/3 简便运算
简便算法(数学):8/13÷7+1/7×6/13 2-6/13 ÷9/26-2/3
2-13分之6÷26分之9=
2-13/6÷26/9-3/2﹙0.75-16/3﹚×﹙9/2+3/1﹚还会有追分的
用简便方法计算!7/3-(6/13÷9/26+3/8) 4/25÷[(2/5+1/3)×9/11] (1/2+2/3-5
2-13分之64÷26分之9-3分之2
2÷[8/9]= [13/16]÷[1/3]= 4÷[2/3]= [2/3]÷[5/6]= [3/4]÷[2/3]= [
解方程[2/3]x÷[1/4]=12 x÷[6/35]=[26/45]÷[13
① 15 16 ÷ 3 8 ÷ 5 6 ② 9 13 ÷ 15 26 × 5 6 ③ 3 5 ÷3+ 1 3 × 4 5
1 8/13÷7+1/7×6/13 2 2-6/13÷9/29-2/3 3 5/12×(5/6+3/4)+4/5